Dinamika Penolakan Pariwisata Halal di Indonesia: Analisis Kepastian Hukum dan Harmonisasi Sosial - Dewi Rahmawati; Sari Efriliyanti; Dewi Ratnasari; Encep Bahru Jaman; Nurul Fadilla (Indo Publishing, 2025)
This study examines the dynamics of resistance to halal tourism in Indonesia, focusing on aspects of legal certainty and social harmony. Although Indonesia has gained global recognition through the Global Muslim Travel Index (GMTI) 2023–2024 as the world’s best Muslim-friendly tourism destination, the domestic implementation of halal tourism has faced resistance in several regions, including Bali, Labuan Bajo (East Nusa Tenggara), and Lake Toba (North Sumatra). Such opposition generally stems from misunderstandings about the essence of halal tourism, which is often perceived as religiously exclusive, as well as from a legal vacuum (recht vacuum) that leaves its implementation unregulated in a comprehensive manner. This research employs a qualitative method with a normative juridical approach, utilizing library research based on legislation, academic journals, and GMTI reports. The findings indicate that the absence of specific regulations has led to legal uncertainty and potential social disharmony within Indonesia’s multicultural society. Therefore, a national regulation that is inclusive and contextual is urgently needed to provide a clear legal foundation, ensure legal certainty for tourism stakeholders, and maintain social harmony within the framework of Indonesia’s diversity.